2009
DOI: 10.1128/jvi.02520-08
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Cytomegalovirus Immediate-Early 1 Gene Is Not Required for Establishment of Latency or for Reactivation in the Lungs

Abstract: The immediate-early protein IE1 of human and mouse cytomegalovirus (MCMV) is one of the first proteins expressed during the productive infection cycle and upon reactivation from latency. The CMV IE1 proteins have been found to inhibit histone deacetylases, suggesting a role in the epigenetic regulation of viral gene expression. Consequently, the IE1 protein is considered to have a profound effect on reactivation, because small amounts of IE1 may be decisive for the switch to lytic replication. Here we asked if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The IE1 protein has long been suspected to be a key player in the events leading to reactivation from hCMV latency although this view has recently been challenged by functional analysis of the mCMV and rCMV IE1 orthologs in mouse and rat models of infection, respectively [37] , [185] . Nonetheless, inflammatory (including allogeneic) immune responses are believed to be efficient stimuli for hCMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The IE1 protein has long been suspected to be a key player in the events leading to reactivation from hCMV latency although this view has recently been challenged by functional analysis of the mCMV and rCMV IE1 orthologs in mouse and rat models of infection, respectively [37] , [185] . Nonetheless, inflammatory (including allogeneic) immune responses are believed to be efficient stimuli for hCMV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In a promonocytic cell-line, ectopic expression of IE1 and IE2 was sufficient for induction of viral early gene expression but not for production of infectious virus [129]. Studies in the mouse and rat models concluded that the IE1 orthologs are not even required for viral reactivation from latency [291][292][293]. Thus, while IE2 is almost certainly necessary for HCMV reactivation (being essential for viral replication) the importance of IE1 in this process remains ambiguous.…”
Section: Role In Viral Replication Latency and Reactivationmentioning
confidence: 99%
“…The difference in the reactivation incidences most likely reflects the difference in the latent viral DNA load (34). As shown recently, although deletion of the regulatory protein IE1 attenuates mCMV (10), an IE1 deletion mutant was still able to reactivate provided that genome loads of WT and mutant virus were adjusted by using higher doses of mutant virus for acute infection (5).…”
mentioning
confidence: 94%